2016
DOI: 10.1177/0363546515626540
|View full text |Cite
|
Sign up to set email alerts
|

Fasciotomy for Deep Posterior Compartment Syndrome in the Lower Leg

Abstract: Fasciotomy was beneficial in 71% of patients with dp-CECS in the lower leg; 47% of study patients experienced a good to excellent outcome. Outcomes were stable in the long term. Persistent complaints were often caused by other untreated conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 25 publications
0
45
1
Order By: Relevance
“…Just half of all operated CECS patients returned to sports practice in one study [14]. One other study of operated dp-CECS patients reported that only 38 % returned to preinjury levels and 41 % performed at lower levels [28]. The present study found that only 30 % were able to resume sports activities at a similar level compared to their preoperative condition, whereas the remaining 70 % performed at a lower level than previously.…”
Section: Discussioncontrasting
confidence: 41%
“…Just half of all operated CECS patients returned to sports practice in one study [14]. One other study of operated dp-CECS patients reported that only 38 % returned to preinjury levels and 41 % performed at lower levels [28]. The present study found that only 30 % were able to resume sports activities at a similar level compared to their preoperative condition, whereas the remaining 70 % performed at a lower level than previously.…”
Section: Discussioncontrasting
confidence: 41%
“…4,20,30 A “fifth compartment” consisting of the tibialis posterior muscle with its own fascia that is left intact during the surgical exploration probably also contributes to an inferior outcome after surgery in patients with dp-CECS. 18,41 In our opinion, a surgeon should always explore all muscles of the affected compartment to make sure the fasciotomy is complete.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most utilised is that developed by Mubarak [16]: a fasciotomy of the anterior and lateral compartments via a 10cm incision. While newer techniques are mini-invasive either via an endoscopic or cutaneous mini-accesses [9][10][11][12][13][14][15][16][17]. These more modern approaches produce results similar to those of interventions using more ample accesses [18].…”
Section: Discussionmentioning
confidence: 99%